Accompanied selfrehabilitation (2015)
Every once in a great while, there arises a young psychiatrist with entirely new rehabilitation ideas for helping patients retrieve their lives from psychosiso Usually such ideas initially cause significant negative reactions from peers but a handful of sturdy physicians continued on to show the world that something different is possible such as George Brooks of Vermont in the U.S., E.E. Antinnen of Finland, and Franco Basaglia of Italy. Now we have to add to this illustrious list, the name of Alberto Fergusson of Colombia, South America. (Extrae of the Forward) Prof Courtenay M. Harding